Two-factor authenticating against app engine from an android app - Boon, Wenjie. (2012)
Single layer authentication solutions have been around since the start of the Internet age. Now as the world shifts towards digital technologies, more and more crucial information is uploaded to the Net. Also with the rapid improvements of processors, making password cracking faster than before, conventional authentication solutions is insufficient to protect the safety of data. It is therefore crucial for us to look into new methods to ensure security. This is where 2 factor authentications come in.